Accuracy of diagnosis and counseling of fetal brain anomalies prior to 24 weeks of gestational age. (18th August 2018) - Snoek, Rozemarijn; Albers, Marieke E. W. A.; Mulder, Eduard J. H.; Lichtenbelt, Klaske D.; de Vries, Linda S.; Nikkels, Peter G. J.; Cuppen, Inge; Pistorius, Lourens R.; Manten, Gwendolyn T. R.; de Heus, Roel
Abstract: Objective: To evaluate the accuracy of prenatal neurosonography in diagnosing underlying causes of fetal ventriculomegaly, posterior fossa anomalies and microcephaly before 24 weeks' gestational age (GA) and to study the accuracy of prenatal counseling on postnatal prognosis. Methods: A retrospective cohort study based on 146 cases of these fetal brain anomalies before 24 weeks' GA. Counseling on prognosis was compared with postnatal outcome. Data on genetic testing was analyzed. Results: Out of 146 cases, 135 (92%) were diagnosed correctly before 24 weeks' GA. Accuracy was 98% (97/99) in cases with multiple anomalies and 81% (38/47) in cases with an isolated abnormality. Counseling on prognosis was correct in 143 out of 146 cases (98%). Prenatal genetic diagnostics detected an anomaly in 51/113 (45%) of cases. In 14/62 (23%) cases prenatal karyotyping was normal, but postnatal array-CGH detected a pathogenic anomaly. Conclusions: Despite the challenges of early gestation, accuracy in diagnosing and counseling fetal brain anomalies before 24 weeks' GA was high. Prenatal genetic testing is a valuable diagnostic tool and should be offered to all women with fetal brain anomalies. Considering the many different types of anomalies and diverse etiologies, a multidisciplinary approach is essential for counseling on postnatal outcome.